2019
DOI: 10.1080/21582041.2019.1618898
|View full text |Cite
|
Sign up to set email alerts
|

Remittances, the diffusion of information and industrialisation in Africa

Abstract: This study examines the role of information and communication technology (ICT) on remittances for industrialisation in a panel of 49 African countries for the period 1980-2014. The empirical evidence is based on three simultaneity-robust estimation techniques, namely: (i) Instrumental Fixed Effects (FE) in order to control for the unobserved heterogeneity; (ii) Generalised Method of Moments (GMM) to account for persistence in industrialisation; and (iii)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 77 publications
4
23
0
Order By: Relevance
“…The limited control variables are adopted to eliminate issues surrounding instrument proliferation that could significantly bias the coefficient estimates. This procedure is consistent with GMMcentric empirical studies that select less than three control variables (Asongu & Odhiambo, 2020c;Kavya & Shijin, 2020). In addition, we expect these control variables to influence tax performance in Sub-Saharan Africa.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…The limited control variables are adopted to eliminate issues surrounding instrument proliferation that could significantly bias the coefficient estimates. This procedure is consistent with GMMcentric empirical studies that select less than three control variables (Asongu & Odhiambo, 2020c;Kavya & Shijin, 2020). In addition, we expect these control variables to influence tax performance in Sub-Saharan Africa.…”
Section: Introductionsupporting
confidence: 80%
“…Following recent GMM-centric literature, the GMM empirical method is used for this present study bearing in mind the specific four factors identified by prior studies (Asongu & Odhiambo, 2020a, 2020cFosu, 2017;Tchamyou, 2019Tchamyou, , 2020a. These fundamental factors include; (i) The number of the countries considered in this study (i.e.…”
Section: Gmm Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study on knowledge transfer, Asongu and Odhiambo (2019c) assessed the role of information diffusion on remittances for industrialisation using a panel of 49 African countries for the period 1980 to 2014. The authors concluded that significant linkages between ICT, remittances and industrialisation were more apparent when initial levels of industrialisation were taken on board in the estimation technique.…”
Section: Building Knowledge Economies In Africamentioning
confidence: 99%
“…Statistics shows that between 2015 and 2020, the real growth rate of gross domestic product of West Africa lagged behind that of East and North Africa (African Economic Outlook, 2019) (See Table 1). The poor industrial performance and by extension weak economic growth and development in West Africa has been attributed to a host of factors including infrastructure deficit (with poor road and transportation network, non-functional ports, inadequate power supply), non-innovative financing options (Onye, Akpama and Ikegwuonu, 2020;Effiom, 2020;Effiom and Agala, 2020), and inadequate capital to finance industrial expansion (Tibebe and Mollick, 2017;Asongu and Odhiambo, 2020). Having reviewed majority of the extant literature on this subject matter, we have not found to the best of our knowledge studies that x-ray the role of institutions in modifying the impact of renewable energy consumption on industrial performance in West Africa.…”
Section: Introductionmentioning
confidence: 99%